Effects of tannic acid on the transport behavior of trivalent chromium in soils and its mechanism. (15th July 2022) - Xu, Teng; Jiang, Xiaofeng; Tang, Yuling; Zeng, Yunhang; Zhang, Wenhua; Shi, Bi
Abstract: Trivalent chromium [Cr(III)] and tannins serve as necessary substances in leather processing and coexist in tannery site, which lead to the chromium contamination in site soil when disposed improperly. However, coexisting tannins are very likely to complex with Cr(III) and affect its properties, ultimately changing the mobility of chromium in soil. In this study, tannic acid (TA) was selected to investigate the complexation with Cr(III) and the influence on the solubility and sorption of Cr(III) in soils. Then, the transport behavior and mechanism of Cr(III)-TA complexes in soil was clarified. Dialysis results showed that the increase of TA concentration and solution pH promoted the formation of complexed Cr(III). The results of UV–Vis absorption spectroscopy, X-ray photoelectron spectroscopy, and density functional theory calculations indicated that the adjacent ionized phenolic hydroxyls in TA functioned as the binding sites with Cr(III) to form the Cr–O bonds and the degree of complexation increased with pH. The Cr(III)-TA complexes had higher solubility than free Cr(III) at pH ≥ 6.0. Batch sorption experiments demonstrated that the sorption capacity of Cr(III)-TA to soils with different pH was always lower than that of free Cr(III). These reasons led to the stronger mobility of Cr(III)-TA in soil columns than Cr(III). Our research reveals that the enhanced mobility of Cr(III) in soils coexisting with TA. Graphical abstract: Image 1 Highlights: Tannic acid (TA) promoted the mobility of Cr(III) in soil. High pH and TA concentration favored the formation of Cr(III)-TA complexes. The structure of complexed chromium changed with increasing pH. The presence of TA significantly improved the solubility of Cr(III) at pH ≥ 6.0. TA weakened the sorption capacity of chromium to soils.